Shocks to Malaysia exports : temporary or permanent? - 375364 Hoffmann, Robert author; Lee, Chew Ging author; Bala Ramasamy author (Kuala Lumpur : University of Nottingham, Malaysia Campus, 2002)
PSZJBL